The Effects of Accentuated Eccentric Loading During Drop Jumps on Strength, Power, Speed and Exercise-Induced Muscle Damage - Bridgeman, Lee Anthony (Auckland University of Technology, 2016)
The overall aim of the thesis was to investigate the acute and chronic effects of accentuated eccentric load (AEL) drop jumps (DJ) on athletic performance and exercise-induced muscle damage (EIMD). Study one assessed the test-retest reliability of a novel multi-joint isokinetic squat device (Exerbotics). The mean concentric peak force (PF) CV and ICC was 10% and 0.95 respectively. The mean eccentric PF CV and ICC was 7.2% and 0.90 respectively. Based on these findings it is suggested that the Exerbotics squat device shows good test-re-test reliability. Study two investigated the relationships between concentric and eccentric PF during the Exerbotics squat and countermovement jump (CMJ) performance. A very large relationship was found between absolute eccentric PF, absolute CMJ peak power (PP) and CMJ height. Based on these findings individuals wishing to enhance their CMJ should include lower body eccentric strength training. Study three assessed the relationships between concentric and eccentric PF, DJs and athletic performance. A large negative relationship was observed between DJ height and sprint times. Based on these findings athletes may benefit from including DJs in their training. Study four investigated the acute effects of AEL DJs on CMJ performance. The 20% AEL condition resulted in greater CMJ height in comparison to all other conditions. The results of this study suggest five DJs with a 20% AEL followed by a two minute recovery period results in a significant enhancement in CMJ height and PP. Study five investigated the effects of 30 and 50 AEL DJs on markers of exercise induced muscle damage including strength, jump performance, muscle soreness (SOR) and creatine kinase (CK) in resistance-trained athletes. In week one baseline CMJ, SJ, concentric and eccentric PF, CK and SOR were assessed. Subjects then completed 30 AEL DJs, and baseline measures were re-tested immediately post, 1, 24 and 48 hours later. Two weeks later the subjects completed the same protocol with an increase in AEL DJ volume (50 jumps). During CMJ testing in week one the subjects jump height was reduced compared to baseline immediately post intervention (ES = -0.38). During SJ testing in week one the subjects jump height was reduced compared to baseline immediately post intervention (ES = -0.24). During squat testing in week one concentric PF was reduced compared to baseline one-hour post intervention (ES = -0.22). During week three testing concentric PF was reduced compared to baseline immediately post intervention (ES = -0.30). During week one eccentric PF was reduced compared to baseline, immediately post intervention, 24 and 48hrs later (ES = -0.31, -0.22 and -0.22). Based on these findings it is proposed that AEL DJs result in minimal EIMD in resistance-trained athletes. In conclusion, it would appear that AEL DJs enhance acute athletic performance with minimal EIMD.
Keywords: Eccentric; Drop jumps; Exercise induced muscle damage; Postactivation potentiation